2011
DOI: 10.1007/s11044-011-9266-7
|View full text |Cite
|
Sign up to set email alerts
|

Graph theoretic foundations of multibody dynamics

Abstract: This is the first part of two papers that use concepts from graph theory to obtain a deeper understanding of the mathematical foundations of multibody dynamics. The key contribution is the development of a unifying framework that shows that key analytical results and computational algorithms in multibody dynamics are a direct consequence of structural properties and require minimal assumptions about the specific nature of the underlying multibody system. This first part focuses on identifying the abstract grap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…The dynamics formulations derived in [7] for rigid-body, serial-chain and tree-topology, multibody systems are examples of SKO models with and φ as the respective SKO and SPO operators. The existence of an SKO model does not depend on any exceptional or unusual features of tree-topology multibody systems.…”
Section: Sko Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…The dynamics formulations derived in [7] for rigid-body, serial-chain and tree-topology, multibody systems are examples of SKO models with and φ as the respective SKO and SPO operators. The existence of an SKO model does not depend on any exceptional or unusual features of tree-topology multibody systems.…”
Section: Sko Modelsmentioning
confidence: 99%
“…To address this gap, part I of this paper [7] introduced the notions of Spatial Kernel Operators (SKO) and the related Spatial Propagation Operators (SPO) . It showed that key spatial operators are in fact instances of SKO and SPO matrices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The notion of SKO models have been shown to provide a general way of deriving a broad range of analytical and algorithmic techniques for tree multibody systems, while requiring few assumptions on the underlying low-level properties of the system [7, 8, 10, 11]. This remarkable consistency persists despite significant differences in the component structure of the corresponding spatial operators across the systems.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, graph techniques have been used to identify general structural properties of tree multibody systems that underlie a broad family of analytical techniques and low-order algorithms for the systems [13-17]. It is seen that tree system dynamics can be described using abstract spatial kernel operator ( SKO ) models , and that several operator results including analytical mass matrix inversion follow directly from the SKO model structure—independent of the specific details of the system.…”
Section: Introductionmentioning
confidence: 99%